2020
DOI: 10.1097/ijg.0000000000001711
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cerebral Vasomotor Reactivity in Patients With Primary Open-angle Glaucoma and Ocular Hypertension Using the Breath-Holding Index

Abstract: Précis: Patients with ocular hypertension (OHT) do not show impaired cerebral vasodilation responses to hypercapnia but patients with primary open-angle glaucoma (POAG) do. Impaired vasoreactivity in patients with POAG may have neuronal or vascular origins and increase stroke risk. Purpose: To investigate changes in cerebral blood flow and cerebral vasomotor reactivity using the breath-holding index in patients with POAG and OHT, to examine whether thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…6 Furthermore, glaucoma is the most common eye disease among people with valvular disease, anemia, and other diseases, and increased cardiovascular mortality has been observed in people with previously diagnosed glaucoma, probably due to the impaired vasodilation response to hypercapnia. [28][29][30] The Early Manifest Glaucoma Trial found that a history of cardiovascular disease is a significant predictor of glaucoma progression. 31 The inconsistency among these studies may be due to differences in the study design or the population characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Furthermore, glaucoma is the most common eye disease among people with valvular disease, anemia, and other diseases, and increased cardiovascular mortality has been observed in people with previously diagnosed glaucoma, probably due to the impaired vasodilation response to hypercapnia. [28][29][30] The Early Manifest Glaucoma Trial found that a history of cardiovascular disease is a significant predictor of glaucoma progression. 31 The inconsistency among these studies may be due to differences in the study design or the population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study speculated that the risk of glaucoma increases by 5% each year after a diagnosis of diabetes, and the association between diabetes and glaucoma could be because they share common mechanisms of vascular dysregulation 6. Furthermore, glaucoma is the most common eye disease among people with valvular disease, anemia, and other diseases, and increased cardiovascular mortality has been observed in people with previously diagnosed glaucoma, probably due to the impaired vasodilation response to hypercapnia 28–30. The Early Manifest Glaucoma Trial found that a history of cardiovascular disease is a significant predictor of glaucoma progression 31.…”
Section: Discussionmentioning
confidence: 99%
“…The ophthalmic artery, middle cerebral artery and posterior cerebral artery, which account for most of the blood supply to the orbit and visual cortex, show reduced blood ow velocities in patients with POAG as measured by transcranial Doppler (Arslan et al, 2021;Harris et al, 2013). Studies conducted by three-dimensional pseudo-continuous arterial spin labeling (3D-pCASL) have demonstrated reduced resting cerebral blood ow (CBF) and reduced visual evoked CBF in the visual cortex in patients with POAG (Wang et al, 2018;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…The ophthalmic artery, middle cerebral artery and posterior cerebral artery, which account for most of the blood supply to the orbit and visual cortex, show reduced blood flow velocities in patients with POAG as measured by transcranial Doppler (Arslan et al, 2021 ; Harris et al, 2013 ). Studies conducted by three-dimensional pseudo-continuous arterial spin labeling (3D-pCASL) have demonstrated reduced resting cerebral blood flow (CBF) and reduced visual evoked CBF in the visual cortex in patients with POAG (Wang et al, 2018 ; Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%